Transient laser-annealing-induced mesophase transitions of block copolymer–resol thin films - Tu, Wei Han (2021)
Block copolymer self-assembly-derived thin films provide direct access to two- and three-dimensional periodically ordered mesostructures as enablers for many nanotechnology applications. This report describes laser-annealing-induced disorder–order mesophase transitions of polystyrene-block-poly(ethylene oxide)/resol hybrid thin films over a range of laser temperatures (∼45 to 525 °C) and short dwell times (0.25 to 100 ms), revealing the non-equilibrium ordering and disordering kinetics and behaviors. We found that a combination of transient laser temperature of ∼275 °C and annealing dwell time of 100 ms provided the most optimal kinetic and thermodynamic control of the diffusivities of hybrid mesophases and photothermal-induced resol polymerization, yielding long-range ordered films resembling an in-plane body-centered cubic sphere morphology. A clear understanding of hybrid thin film mesophase self-assembly under non-equilibrium laser annealing could open new avenues to introduce novel chemistries and rapidly achieve nanoscale periodic order suitable for the patterning of complex structures, electronics, sensing, and emerging quantum materials.